THE EFFECT OF INNOVATIVE POTENTIAL ON SMALL BUSINESS PERFORMANCETHE EFFECT OF INNOVATIVE POTENTIAL ON SMALL BUSINESS PERFORMANCE - Matejun, Marek (PEOPLE: International Journal of Social Sciences, 2017)
The aim of the paper is to describe and identify the level of innovative potential of micro, small and medium-sized enterprises (SMEs) and to assess its impact on small business performance. Three research questions were formulated. The author's empirical research in the form of a survey conducted on a sample of 1,741 SMEs in the European Union Member States served the aim of the paper. The measurements were based on an original synthetic index of small business innovative potential (6 items, alpha Cr. = 0.841) structured with respect to three areas: the social area, the area of the company's creative competencies and the area of business opportunities. The results obtained indicate a moderate level of innovative potential of the surveyed companies which increases significantly as the size of the enterprises grows. The innovative potential significantly and positively influences the level of small business performance, with a stronger impact on qualitative than quantitative performance